2017
DOI: 10.1002/anie.201610921
|View full text |Cite
|
Sign up to set email alerts
|

Bis(aminoaryl) Carbon‐Bridged Oligo(phenylenevinylene)s Expand the Limits of Electronic Couplings

Abstract: Carbon-bridged bis(aminoaryl) oligo(para-phenylenevinylene)s have been prepared and their optical, electrochemical, and structural properties analyzed. Their radical cations are class III and class II mixed-valence systems, depending on the molecular size, and they show electronic couplings which are among the largest for the self-exchange reaction of purely organic molecules. In their dication states, the antiferromagnetic coupling is progressively tuned with size from quinoidal closed-shell to open-shell bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Now, while the longer chain oligomers achieved excellent laser performance, COPV1 showed weaker ASE performance, with a rather high threshold of 90 kW cm −2 and a lifetime of only 1.8 × 10 2 pp. The instability problems were attributed to the reactive terminal sites of the photoexcited states . In this work, our hypothesis is that through polymerization, the terminal sites of COPV1 would be protected (in a similar way to the longer COPV homologues which have a smaller distribution of terminal sites and thus higher photostability) so its photostability would improve.…”
Section: Introductionmentioning
confidence: 93%
“…Now, while the longer chain oligomers achieved excellent laser performance, COPV1 showed weaker ASE performance, with a rather high threshold of 90 kW cm −2 and a lifetime of only 1.8 × 10 2 pp. The instability problems were attributed to the reactive terminal sites of the photoexcited states . In this work, our hypothesis is that through polymerization, the terminal sites of COPV1 would be protected (in a similar way to the longer COPV homologues which have a smaller distribution of terminal sites and thus higher photostability) so its photostability would improve.…”
Section: Introductionmentioning
confidence: 93%
“…[32] In general, delocalized (Robin-Day class-III) derivatives possess an asymmetric and narrow lowest energy band, while in localized (Robin-Day class-II) derivatives the lowest energy band results from an intervalence charge transfer (IV-CT) with a well-defined symmetric Gaussian shape. [64] For that reason, Ito and co-workers concluded that compound III + is a fully delocalized Robin-Day class-III derivative and assumed an electronic coupling V ofṽ IVCT max 2 = 2608 cm À1 . [32] However, our TD-DFT computations on the monocations 7 + and 8 + , with a specially adjusted functional (BLYP with 35 % exact HF exchange [65] ), show that the lowest energy excitation is a result of the promotion of an electron from the b-HOMO to the b-LUMO orbital and these orbitals show the expected phase behavior for localized Robin-Day class-II compounds (Figure 7).…”
Section: Spectroelectrochemistrymentioning
confidence: 99%
“…Their interesting properties have fueled their development for potential applications in optoelectronics, [1,2] nonlinearo ptics, [3,4] spintronics [5] and organic photovoltaics. [9][10][11][12][13][14][15][16] Aminiumi ons are isoelectronic to carbon and the highere lectronegativity of the nitrogen atom contributes to their high stability in the biradicalf orm. [9][10][11][12][13][14][15][16] Aminiumi ons are isoelectronic to carbon and the highere lectronegativity of the nitrogen atom contributes to their high stability in the biradicalf orm.…”
mentioning
confidence: 99%